Gênese hidrotermal do minério de ferro da jazida Minerita, porção sudoeste da Serra do Curral, Quadrilátero Ferrífero, Minas Gerais - Anna Elisa Pacheco Furlan Jonas (2019)
The southwestern portion of the Serra do Curral is located in the low deformation domain of the Quadrilátero Ferrífero region, where hypogene, high-grade iron ores are associated with sulfides and controlled by shear and fold zones. Quartz, dolomite and amphibole itabirites dominate in this area, with the former constituting the main host rock to ore. Rocks are folded, refolded, and present reverse stratigraphy of the Minas Supergroup units. The Minerita deposit is located within this structural complexity. The main lithotypes described in Minerita are hydrothermally altered quartz itabirites, characterizing distal and intermediate alteration zones, with iron ore representing the proximal zone. Mineral parageneses of itabirites and iron ore mainly include kenomagnetite, martite and anhedral hematite, recrystallized and vein quartz. A sulfide breccia is also present; it contains magnetite, anhedral hematite, pyrite, chalcopyrite, recrystallized and vein quartz, as well as fine- to medium-grained carbonate. Hydrothermal alteration of itabirites results in martitization with formation of anhedral hematite, leaching of silica and localized silicification with abundant veining. LA-ICP-MS results in iron oxides suggest that, during martitization, a small gain in Al, Cr, Ga, Pb and REE + Y occurred, with losses in Mg, Zn, Mn, Co and V. During the formation of anhedral hematite, gains of Al, Cr, V and Zn, and losses in Mg, Ti, Mn, Co, Pb and REEs + Y are recorded. For magnetite and anhedral hematite in sulfide breccia, there was significant enrichment of Zn, Ga and Pb, and impoverishment of V and REEs + Y. Sulfur isotope results indicate a magmatic origin for pyrite in the sulfide breccia. In contrast, fluid inclusion microthermometry in vein quartz of iron ore reflects the involvement of at least one low-temperature (between 108 °C and 142 °C) fluid with low to moderate-salinity (0 to 14.26 % in weight of NaCl eq.). Mineralization, itabirite enrichment and formation of sulfide breccia may have resulted from the interaction between basinal fluid and meteoric water, in addition to subordinate metamorphic fluid as previously indicated for other iron deposits in the region. The involvement of either intrusive country rocks or rocks from the Rio das Velhas Supergroup may explain the magmatic sulfur signature.